2017
DOI: 10.1142/s0219633617500572
|View full text |Cite
|
Sign up to set email alerts
|

Combined experimental and theoretical studies on molecular structures, spectroscopy of 4-(3-(2-amino-3,5-dibromophenyl)-1-(benzoyl)-4,5-dihydro-1H-pyrazol-5-yl)benzonitriles through NBO, FT-IR, HOMO-LUMO and NLO analyzes

Abstract: The pyrazole compounds 4-(3-(2-amino-3,5-dibromophenyl)-1-(4-substitutedbenzoyl)-4,5-dihydro-1H-pyrazol-5-yl) benzonitriles (4–6) have been synthesized and characterized by elemental, IR, 1HNMR spectral methods. In addition, the synthesized compounds were subjected to density functional theory for further understanding of the molecular architecture and optoelectronic properties. The optimized geometric parameters were in support of the corresponding experimental values. The FT-IR spectra of 4–6 have been inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The results were compared with the geometries of 4-(3-(2-amino-3,5-dibromophenyl)-1-(4-nitrobenzoyl)-4,5-dihydro-1 H -pyrazol-5-yl)benzonitrile predicted at the same level of theory. 28 The calculated C3–N7 bonds were 1.299, 1.298, 1.300, 1.299, 1.299 and 1.298 Å for M1–M6 , respectively, in agreement with the 1.299 Å calculated for Ma . This type of bond has been experimentally observed to be 1.275 Å and calculated to be 1.287 Å for bis-spiropipridinon/pyrazole derivatives.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The results were compared with the geometries of 4-(3-(2-amino-3,5-dibromophenyl)-1-(4-nitrobenzoyl)-4,5-dihydro-1 H -pyrazol-5-yl)benzonitrile predicted at the same level of theory. 28 The calculated C3–N7 bonds were 1.299, 1.298, 1.300, 1.299, 1.299 and 1.298 Å for M1–M6 , respectively, in agreement with the 1.299 Å calculated for Ma . This type of bond has been experimentally observed to be 1.275 Å and calculated to be 1.287 Å for bis-spiropipridinon/pyrazole derivatives.…”
Section: Resultssupporting
confidence: 77%
“…The results have indicated inter- and intra-molecular delocalization and acceptor–donor interactions based on second-order perturbation interactions; moreover, polarizability and hyperpolarizability calculations have indicated that the compounds possess good NLO properties. 28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 depicted the ligand's mass spectrum and described its monomeric structure 25 . A molecular ion peak at m / z = 436.13 amu in the spectrum was found to represent the anhydrous parent molecular weight.…”
Section: Results and Analysismentioning
confidence: 99%
“…NLO is at the forefront of current research because it provides the key functions of frequency shifting, optical modulation, optical switching, optical logic and optical memory for the emerging areas such as telecommunications, signal processing and optical interconnections [Bharathi et al 2017;Srinivasan et al 2015]. In discussing nonlinear optical properties, the polarization of the molecule by an external radiation field is often approximated as the creation of an induced dipole moment by an external electric field.…”
Section: Non-linear Optical (Nlo) Analysismentioning
confidence: 99%